Residue-Specific Incorporation of the Non-Canonical Amino Acid Norleucine Improves Lipase Activity on Synthetic Polyesters - Haernvall, Karolina; Fladischer, Patrik; Schoeffmann, Heidemarie; Zitzenbacher, Sabine; Pavkov-Keller, Tea; Gruber, Karl; Schick, Michael; Yamamoto, Motonori; Kuenkel, Andreas; Ribitsch, Doris; Guebitz, Georg M.; Wiltschi, Birgit (Frontiers in Bioengineering and Biotechnology, 2022)
Environmentally friendly functionalization and recycling processes for synthetic polymers have recently gained momentum, and enzymes play a central role in these procedures. However, natural enzymes must be engineered to accept synthetic polymers as substrates. To enhance the activity on synthetic polyesters, the canonical amino acid methionine in Thermoanaerobacter thermohydrosulfuricus lipase (TTL) was exchanged by the residue-specific incorporation method for the more hydrophobic non-canonical norleucine (Nle). Strutural modelling of TTL revealed that residues Met-114 and Met-142 are in close vicinity of the active site and their replacement by the norleucine could modulate the catalytic activity of the enzyme. Indeed, hydrolysis of the polyethylene terephthalate model substrate by the Nle variant resulted in significantly higher amounts of release products than the Met variant. A similar trend was observed for an ionic phthalic polyester containing a short alkyl diol (C5). Interestingly, a 50% increased activity was found for TTL[Nle] towards ionic phthalic polyesters containing different ether diols compared to the parent enzyme TTL[Met]. These findings clearly demonstrate the high potential of non-canonical amino acids for enzyme engineering.